The importance of anatomical zonal classification in the early management of penetrating neck injuries - Al-Assal, Khalid D.; A Thuhabat, Jawad; A Al-Khafaji, Ahmed (AL-Kindy College Medical Journal, 2020)
Background: Penetrating neck injuries are common problem in our country due to increasing violence, terrorist bombing and military operations. These injuries are potentially life threating and need great attention and proper management. Objective: The aim of this study is to focus on the importance of anatomical zonal classification of the neck in the management of penetrating injuries of the visceral compartment of the Neck. Methods :70 patients with various injuries who were managed at causality unit and Otolaryngology department in Al-Kindy Teaching Hospital during aperiod from January 1st 2015 to October 31st 2015. The study carried on those patient depending on proper clinical examination and their urgent management. Results : Both civilian and military patients were admitted to the hospital, 34 patients (47.2%) in their 20s age group, while only 2 (2.8%) in 60s. High percentage of penetrating neck injuries in zone , 48 patient (68.6%) and lowest in zone , 6 patients (8.5%). 40 patients (57.1%) presented with tracheal and laryngeal injuries and 12 patients (17.5%) were with pharyngeal injuries, 4 patients (5.7) were with recurrent laryngeal nerve injury and 13 patients (18.5%) presented with vascular injuries. Radiological examination done for 53 patients (75%) and we found foreign bodies in 30 patients (56.6%), tracheal deviation in 4 patients (7.5%) and emphysema in 19 patients (35.8%). Tracheostomy done in 51 patients (72.8%) neck, exploration in 20 patients (28.5%) and a 9 patients (12.8%) treated conservatively. Conclusion: Zonal classification of penetrating neck injuries was helpful in the management. Our study explains demographics and location of the injuries. Young men involved in violence and bombing was at high risk. Zone with involvement of trachea, larynx and pharynx were most common areas of injuries. Recommendations Anatomical zone classification should be used as a guideline in management of penetrating neck injuries. (Trauma lifesaving guideline).Tracheostory should be practiced by every doctor in casualty unit. Team of surgeons and anaesthiologist should be always ready for any intervention with patient present to the casualty unite with a penetrating neck injury. Emergency medicine medical practice must be presents in every casualty unit to deal with insults. Aim of the study 1.To recognize penetrating injuries of the neck according to the anatomic neck zones. 2.Identify the outcome of their treatment